Occurence of multidrug resistant Staphylococcus aureus in horses in Malaysia - Zakaria, Zunita; Fateh Mohamed, Bashir Ahmad; Ahmad, Mohd Hafizal (Veterinary World, 2008)
A total of 22 Staphylococcus aureus were isolated from 50 samples from 8 stable horses. They are positive in the catalase and coagulase tests. Upon testing the cultures with SLIDEX test kit all formed agglutination within a few seconds, confirming they are of S. aureus. When cultured onto MSA, all isolates formed yellow colonies. However, none of the isolates produced blue colonies on ORSAB indicating that there were no MRSA among the S. aureus. There were 13 isolates which were multiresistant. Eleven are resistant to eight out of ten antibiotics tested. All these isolates were found to originate from stable G. One isolate is resistant to 5 antibiotics while another one isolate is resistant to 3 antibiotics. The rest of the isolates are not multiresistant to the antibiotics tested.